Ideas for Comillas for the protection and improvement of the town and its surroundings (Ciudades, 2018)
The town of Comillas faces the challenge of reconciling the turistic whirlpool with the daily activity in an urban context plenty of cultural and landscape values. This text makes reference to the suggested proposals for the development of Comillas, as a guidance to solve the spatial contradiction found in the confluence of the traditional town and the recent growths, which generates several different problems related to mobility and traffic, a local urban growth lacking a strong infrastructural system, and a misuse of the traditional space. The solution for the town of Comillas includes creating an “urban structure” which restores the historical town space and simultaneously reconstructs the most recent urban growths and makes possible the future ones.
Keywords: touristic characterization; traditional city restoration; sustainable development; public urban structure; mobility system